Water column raw data (Kongsberg EM 122 working area dataset) of RV MARIA S. MERIAN during cruise MSM112/2 - Gavin D extquotesingleMello; Gustavo Binda Souza; Frank Nitsche (PANGAEA, 2023)
Water column raw data using the ship extquotesingles own Kongsberg EM 122 multibeam echosounder was recorded on 9 days between 2022-11-25 and 2022-12-03 RV MARIA S. MERIAN cruise MSM112/2 in the Atlantic Ocean. The data are archived at the Mass Data Management System and published together with the corresponding .all data files https://doi.org/10.1594/PANGAEA.957210. This data publication is conducted within efforts of the German Marine Research Alliance in the core area extquotesingleData management and Digitalization extquotesingle (Deutsche Allianz Meeresforschung, DAM). The data quality is unknown.